Design of a Monitoring System for the Number of Visitors and Room Temperature Telkom Plaza Bengkulu - suwarto, suwarto; Riska, Riska; Mardiana, Yessi (Internet of Things and Artificial Intelligence Journal, 2024)
The development of Internet of Things (IoT) technology has brought significant impacts on various aspects of life, including the management and monitoring of public facilities. One of the public facilities that requires monitoring the number of visitors isTelkom Plaza Bengkulu. The main problem atTelkom Plaza Bengkulu is the absence of an effective monitoring system that tracks the number of visitors and room temperature in real time. The purpose of this research is to design a system that can monitor the number of visitors and room temperature automatically, help management make decisions, and optimize services. The research is expected to contribute to the development of information technology in the management of public facilities in the digital era. The method used is an experimental method to design an IoT-based monitoring system. This system uses PIR and DHT22 sensors as input for ESP32, then displays data on the number of visitors and room temperature in real-time through the website and smartphone application using the Blynk IoT platform, as well as automatic fan operation based on room temperature. The test results show the success of the IoT-based monitoring system for the number of visitors and room temperature of Plaza Telkom. The PIR sensor detects movement up to a distance of 2 meters. DHT22 sensor measures temperature with an accuracy of ±0.02%. The relay module controls the fan responsively. Blynk dashboard displays real-time data. The user interface works on laptops and smartphones, providing consistent access and display. An IoT-based monitoring system for the number of visitors and room temperature forTelkom Plaza Bengkulu was successfully designed and implemented. This system fulfills the research objectives and can be applied in other Plaza Telkom locations, although there is still a need for improvement and room for further development.